Leitourgia The Missing Link in Evangelii Gaudium - McGregor, Peter John (2019)
Some especially insightful and challenging passages in Evangelii Gaudium are those on the importance of a personal encounter with Jesus, the evangelizing power of popular piety, person to person witness, and the need for the power of the Holy Spirit. However, in order to do full justice to the mission of the Church, the document requires more on the priestly aspect of this mission. This element is substantially absent, in part, because of Francis's veneration of Evangelii Nuntiandi. However, this absent element can be obtained from the missiology of Lumen Gentium, John Paul II, and the Catechism of the Catholic Church. Based on an analysis of the meaning of leitourgia in the New Testament, this article concludes that this missing element can serve as a link between Pope Francis's kerygma and diakonia, enabling a harmony which has been missing, to greater or lesser degrees, from the Church's mission in the 20th and 21st centuries.
Keywords: Evangelii Gaudium; John Paul II; Pope Francis; Diakonia; Kerygma; leitourgia